2020
DOI: 10.1002/bab.1918
|View full text |Cite
|
Sign up to set email alerts
|

Di‐2‐picolylamine triggers caspase‐independent apoptosis by inducing oxidative stress in human liver hepatocellular carcinoma cells

Abstract: Di‐2‐picolylamine (DPA) is an organic compound that has been shown to possess antioxidant properties when conjugated to form a metal complex. The basis of this study was to determine the effects of DPA on the proliferation and apoptosis of human hepatocellular carcinoma cells and elucidate the possible mechanisms. The methylthiazol tetrazolium assay served to measure cell viability and generated an IC50 of 1591 µM. Luminometry was used to investigate caspase activity and ATP concentration. It was observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The activation of caspase-3 is a central event in the process of apoptosis (Budihardjo et al 1999 ; Thornberry and Lazebnik 1998 ; Wolf and Green 1999 ). This cysteine protease, which is proteolytically activated by the cleavage of pro-caspase-3 by caspase-8, cleaves several intracellular proteins (Madide et al 2021 ; Thornberry et al 1997 ). Therefore, the results confirmed that the Clk inhibitor could more severely induce apoptosis of CRC cells overexpressing CLASRP.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of caspase-3 is a central event in the process of apoptosis (Budihardjo et al 1999 ; Thornberry and Lazebnik 1998 ; Wolf and Green 1999 ). This cysteine protease, which is proteolytically activated by the cleavage of pro-caspase-3 by caspase-8, cleaves several intracellular proteins (Madide et al 2021 ; Thornberry et al 1997 ). Therefore, the results confirmed that the Clk inhibitor could more severely induce apoptosis of CRC cells overexpressing CLASRP.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, the buffer was discarded followed by blocking the membrane with 5% BSA for 2 h. HRP-conjugated house-keeping antibody β-actin (abd1214) (1:5000 dilution in 5% BSA/TTBS 1 h) was then added. After successive washes in TTBS, the membrane was viewed as described previously (Madide et al, 2020).…”
Section: Protein Transfermentioning
confidence: 99%
“…Di‐2‐picolylamine (DPA) is an organic compound that consists of 2 picolyl groups substituted with amine groups on each side. The nitrogen atoms on the picolyl groups are the atoms that have been proven to have anticancer activities [30] . Thus, DPA and N ‐substituted DPA derivatives have been investigated for their anticancer activities against malignant cells [31] .…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen atoms on the picolyl groups are the atoms that have been proven to have anticancer activities. [30] Thus, DPA and N-substituted DPA derivatives have been investigated for their anticancer activities against malignant cells. [31] With respect to the literatures, structural design of carbazole probes with substituents at the 9 th position and their molecular interactions with G4 DNAs have been rarely discussed.…”
Section: Introductionmentioning
confidence: 99%